Global and local information asymmetries, illiquidity and SEC Rule 144A/Regulation S: The case of Indian GDRs - Michael Pinegar, J; Ravichandran, R (Journal of Banking & Finance, 2002)
Between 1992 and 1997, Indian firms were the most frequent issuers of equity-backed Global Depositary Receipts (GDRs) governed by the SEC's Rule 144A and Regulation S. They also accounted for the highest dollar volume. Home-market stock price responses to these issues are consistent with the hypotheses that GDRs enable firms to resolve two forms of information asymmetry: (1) an asymmetry between issuing firms and international investors that results from market segmentation and (2) an asymmetry between Indian firms and home-market investors that resembles asymmetries that help explain abnormal returns in equity private placements by US firms. Our evidence suggests that GDR issuance can increase investors' recognition of underlying shares even if there are no liquidity enhancements and even if disclosure requirements are not as demanding as those imposed on foreign firms whose depositary receipts trade in public US markets.